О бычках семейства Gobiidae кавказских рек бассейна Черного моря - Пинчук, В.И. (Вестник зоологии, 1969)
The Caucasian rivers of the Black Sea basin as habitats of the Gobiidae representatives can be divided into some groups. Proterorhinus marmoratus Pall, was found in mauntain Caucasian rivers for the first time. Gobus cephalarges constructor (Nor dm.) as to the structure of head takes an intermediate place between G. cephalarges from the north-western part of the Black Sea and the Azov form of G. cephalarges-, as to the size of a sucker it is closer to G. platyrostris, but is distinguished from the latter by the hiatus in the head structure. The river schools of G. cephalarges constructor differ from each other in size of eyes and form of body.